IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI PEMBANGUNAN DAERAH (SIPD) DALAM PERENCANAAN PEMBANGUNAN DAERAH PADA PEMERINTAH DAERAH KABUPATEN ASMAT - Yosephus Yacobus David; Yosephina Ohoiwutun (Universitas Cenderawasih, 2022)
This research is entitled Implementation of Regional Development Information System (SIPD) Policy in Regional Development Planning in the Asmat Regency Government. The Regional Development Information System Policy aims to provide facilities and the availability of data and information systems to stakeholders to make decisions and development planning policies at the regions or at the center. This study aims to determine and analyze how the implementation of the Regional Development Information System policy and what are the inhibiting and supporting factors in regional development planning in the Asmat Regency Government. The research locus is at the Regional Development Planning Agency and Regional Development Research and other Regional Apparatus Organizations. This study uses a qualitative method with a descriptive approach. The implementation of the policy of the Minister of Home Affairs Regulation Number 70 of 2019 is assessed by four variables, namely: communication, resources, disposition and bureaucratic structure. There are two variables that become inhibiting factors, namely: resources, staff or human resources of the Regional Development Planning and Research Agency have fulfilled and understood, while the Regional Apparatus Organizations are constrained by the number of implementers who understand and other resources in the form of network access internet network connectivity, while the bureaucratic structure, the absence of a regional head decision regarding the Asmat Regency Data Management Team, the division of tasks and functions that are not in accordance with the accounts in the application resulted in duplicate duties and functions of the implementer so that the input delay was in accordance with the schedule for the preparation of planning documents. Furthermore, there are two supporting variables, namely: communication, the Development Planning Agency and Regional Development Research as the manager of the Regional Development Information System application has carried out communication smoothly with other Regional Apparatus Organizations and internally themselves. The clarity of the orders given by the head of the Regional Development Planning and Research Agency to the heads of fields to carry out their duties and functions as well as consistency in communicating with Regional Apparatus Organizations in accordance with their field of affairs, as well as disposition variables, the attitude of the implementers are responsive and in accordance with the direction of the leadership. The results and discussion of research in the implementation of regional development information system policies in regional development planning at the Asmat Regency Government are assessed in accordance with the Regulation of the Minister of Home Affairs Number 70 In 2019 by following the stages of inputting the preparation of regional development planning documents on an application in the form of a website, namely the Regional Development Information System